IoT based Disabled Parking System (DiParkSys) v2.0 Arduino Uno / R.A. JM Gining ... [et al.] - Gining, R.A. JM; Fauzi, S.S.M; Razak, T.R; Jamaluddin, M.N.F; Fuad, M.N.M; Zaki, N.A; Maskat, R. (Universiti Teknologi MARA, Perlis, 2021)
The urbanization in the urban area can lead to many effects, and one of them is limited parking space. In the context of disabled parking spaces, many easily violate that allocated spaces without guilty. For the authorities to monitor the violation of the disabled parking spaces are quite challenging. That is, the authorities would still need to look out for the parking violation by manually observing and looking around, in other words, through their observation. The purpose of this study is to improve the current Disabled Parking System (DiParkSys) v2.0 by integrating it with GSM notification system. The GSM module assembled in DiParkSys will immediately notify authorities of any violation by giving the coordinate of the violated parking slot. The prototype was first designed using system visualization and schematic diagram. The integration between the alarm and GSM module was then validated using an integration test before the functionality of the prototype was tested using a Test Cases method.